Pengaruh Penggunaan Media Webblog Berbasis HOTS Terhadap Motivasi dan Hasil Belajar Pada Materi Laju Reaksi - Bernika Evelyn Sibarani; Marham Sitorus (Universitas Negeri Medan, 2021)
This reseach goals to determine how the effect of knowing the effect of using Webblog media on the HOTS Evaluation Based Problem Based Learning Model on Motivation and Student Learning Outcomes in the Material of Reaction Rate. The research method used was an experiment that was modified as needed. The sampling technique used is by using a purposive technique where class XI IPA 4 as an experimental class is taught using Webblog Media in the Problem Based Learning model using and XI IPA 5 as a control class that is taught using Power Point Media in the Problem Based Learning learning model based on HOTS evaluation . The analysis technique used is the mean difference test, the percent increase in learning outcomes, normality test, homogeneity test and hypothesis testing. The results obtained by the average value of the experimental and control classes in the pretest data were 36.25 and 27.25. The post-test scores for the experimental and control classes were 79 and 65.5. Data on the normality and homogeneity test obtained data were normally distributed and the data were homogeneous. The correlation test for the effect of using Webblog media in the Problem Based Learning model on student motivation and learning outcomes is the value of rxy = 0.754 which means there is a positive correlation between motivation and student learning outcomes.